2015
DOI: 10.1645/14-621.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variability and Molecular Identification ofUncinariaspp. (Nematoda: Ancylostomatidae) from Grizzly and Black Bears: New Species or Phenotypic Plasticity?

Abstract: The hookworms Uncinaria rauschi Olsen, 1968 and Uncinaria yukonensis ( Wolfgang, 1956 ) were formally described from grizzly ( Ursus arctos horribilis) and black bears ( Ursus americanus ) of North America. We analyzed the intestinal tracts of 4 grizzly and 9 black bears from Alberta and British Columbia, Canada and isolated Uncinaria specimens with anatomical traits never previously documented. We applied morphological and molecular techniques to investigate the taxonomy and phylogeny of these Uncinaria paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Recent epidemiological surveys revealed that some wild animal-derived species of Ancylostoma are emerging as important helminthic zoonotic agents because of rapid urbanization and increased human-wildlife interactions [11, 1321]. The giant panda, for example, is an endangered and rare wild species in China that has been artificially protected and even partially housed for decades due to habitat loss [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent epidemiological surveys revealed that some wild animal-derived species of Ancylostoma are emerging as important helminthic zoonotic agents because of rapid urbanization and increased human-wildlife interactions [11, 1321]. The giant panda, for example, is an endangered and rare wild species in China that has been artificially protected and even partially housed for decades due to habitat loss [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the hookworm Uncinaria yukonensis (Wolfgang, 1956) was characterized in black bears and Uncinaria rauschi (Olsen, 1968) in grizzly and black bears [81, 82]. On the basis of comparisons of morphometric and distribution data of ursine hookworms as well as the historical biogeography of bears, Catalano et al [13] proposed that there was a relatively recent host-switching event of U. rauschi from black bears to grizzly bears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important hookworm species in black bears is Uncinaria rauschi, which can reach up to 72% prevalence in some areas of Canada (Catalano et al., 2015a, Catalano et al., 2015b). Uncinaria yukonenesis is more common in brown bears in North America, while in Japan brown bears are infected with Ancylostoma malayanum (Catalano et al., 2015a, Catalano et al., 2015b, Asakawa et al., 2006).…”
Section: Mammalian Orders and Families Infected With Hookwormsmentioning
confidence: 99%
“…The most important hookworm species in black bears is Uncinaria rauschi, which can reach up to 72% prevalence in some areas of Canada (Catalano et al., 2015a, Catalano et al., 2015b). Uncinaria yukonenesis is more common in brown bears in North America, while in Japan brown bears are infected with Ancylostoma malayanum (Catalano et al., 2015a, Catalano et al., 2015b, Asakawa et al., 2006). The canine hookworm, A. caninum, and the raccoon hookworm, A. lotoris, infect black bears in the southeastern United States; however, the mean intensities are usually low (<15 nematodes per animal) (Crum et al., 1978, Foster et al., 2011).…”
Section: Mammalian Orders and Families Infected With Hookwormsmentioning
confidence: 99%